2014
DOI: 10.4103/0019-5154.139872
|View full text |Cite
|
Sign up to set email alerts
|

Topical steroid-damaged skin

Abstract: Topical steroids, commonly used for a wide range of skin disorders, are associated with side effects both systemic and cutaneous. This article aims at bringing awareness among practitioners, about the cutaneous side effects of easily available, over the counter, topical steroids. This makes it important for us as dermatologists to weigh the usefulness of topical steroids versus their side effects, and to make an informed decision regarding their use in each individual based on other factors such as age, site i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 10 publications
2
53
0
1
Order By: Relevance
“…The increased cell density in epidermal layers after steroid treatment seems to contrast with earlier reports on antiproliferative effects of steroids and an overall loss of cells in vitro and in vivo. 36,[41][42][43] It can be assumed that a reduction of the total number of cells occurs with a simultaneously increasing cell density due to the loss of intercellular matrix and ground substance, resulting in an overall reduction of epidermal and dermal tissue volume.…”
Section: Discussionmentioning
confidence: 99%
“…The increased cell density in epidermal layers after steroid treatment seems to contrast with earlier reports on antiproliferative effects of steroids and an overall loss of cells in vitro and in vivo. 36,[41][42][43] It can be assumed that a reduction of the total number of cells occurs with a simultaneously increasing cell density due to the loss of intercellular matrix and ground substance, resulting in an overall reduction of epidermal and dermal tissue volume.…”
Section: Discussionmentioning
confidence: 99%
“…Potent topical corticosteroid preparations used for long periods or in excessive quantities may lead to skin atrophy as a well-recognized dermatological risk (18)(19)(20). Corticosteroid-induced skin atrophy is a consequence of collagen synthesis inhibition in connective tissue (18).…”
Section: Discussionmentioning
confidence: 99%
“…However, the incidence of adverse effects due to clobetasol cream was about 42% in this study probably due to d respondents. Study showed hypertrichosis and dermatrophy as common adverse effects due to clobetasol [18,19,20] (Fig. 3).…”
Section: Studies Conducted In Various Countries Includingmentioning
confidence: 97%